Theories of justice underpinning equity in education for refugee and asylum-seeking youth in the U.S.: considering Rawls, Sandel, and Sen. Issue 3 (2nd July 2020) - Ward, Catherine
ABSTRACT: This paper probes theories of justice underpinning the concept of equity to deconstruct the term and ascertain how best to equitably support refugee and asylum-seeking youth in U.S. schools. Building upon theories posited by John Rawls, Michael Sandel, and Amartya Sen, the paper aims to extend beyond ideal theory into a theoretical framework of equity with operationalizing potential. Recognizing refugee and asylum-seeking youth as part of the U.S. social contract and therefore bound to government support, the paper represents that equitable education for these young people in our globalized world is essential from both a human rights and economic perspective. Such equitable education will only be achieved when universal minimum standards are offered to everyone and made inclusive, so that all are invited to fully participate as culturally respected learners and knowledge producers in academic spaces.